2015
DOI: 10.1016/j.biopsycho.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent mismatch negativity deficits across deviant types in early illness schizophrenia-spectrum patients

Abstract: Neurophysiological abnormalities in auditory deviance processing, as reflected by the mismatch negativity (MMN), have been observed across the course of schizophrenia. Studies in early schizophrenia patients have typically shown varying degrees of MMN amplitude reduction for different deviant types, suggesting that different auditory deviants are uniquely processed and may be differentially affected by duration of illness. To explore this further, we examined the MMN response to 4 auditory deviants (duration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 91 publications
9
34
1
3
Order By: Relevance
“…deviants. Such averaging is consistent with the group analysis approach applied to MMN data in other CHR [31] and schizophrenia [19] studies.…”
Section: Variance Components and G-coefficientssupporting
confidence: 84%
“…deviants. Such averaging is consistent with the group analysis approach applied to MMN data in other CHR [31] and schizophrenia [19] studies.…”
Section: Variance Components and G-coefficientssupporting
confidence: 84%
“…The MMN is a widely studied ERP component that reflects pre-attentive processing of the relationship between successive auditory stimuli at the level of the auditory cortex 2634 . It is elicited most commonly in the context of an auditory oddball paradigm, in which a sequence of repetitive identical stimuli (‘standards’) is interrupted infrequently and unexpectedly by a physically different, deviant (‘oddball’) stimulus.…”
Section: Behaviour and Neurophysiologymentioning
confidence: 99%
“…As with tone matching deficits, the degree of deficit in MMN generation is as large as it is in other well-validated neurocognitive tests, such as tests of executive processing or working memory 30,31 . Deficits in MMN generation in schizophrenia have been reported for multiple types of deviants, including pitch, duration or intensity 32 , with little difference in the degree of deficit to different deviance types 3234 .…”
Section: Behaviour and Neurophysiologymentioning
confidence: 99%
“…Hay et al, 2015 [25] reported that that neurophysiological mechanisms underlying processing of auditory deviants are compromised early in the illness, and these deficiencies are not specific to the type of deviant presented.…”
Section: Deviancementioning
confidence: 97%